Detection of creep degradation during pressure vessel testing using electromagnetic sensor technology. (2nd November 2017) - Wilson, John W.; Allen, David J.; Peyton, Anthony J.; Shibli, Ahmed; Davis, Claire
Abstract: 9%Cr steels have been in use in power generation for over 20 years. Over this time, there have been a number of incidents of failure by Type IV cracking at welds initiating sub-surface, making surface inspection procedures unsuitable for crack detection. Replication to identify creep cavitation damage can potentially give an early warning of imminent cracking, but has proved unsuccessful in high Cr martensitic steels. Electromagnetic (EM) inspection can provide fast inspection of welded components with minimal surface preparation and some increase in inspection depth. This paper shows the results of accelerated creep tests carried out on a P91 pressure vessel, with EM inspections during regular test interruptions. The results show that EM inspection gave indications of damage in the latter stages of creep cavitation. EM is considered to have the potential for quick assessment of component through thickness damage, flagging up locations of potential problems for more detailed investigation.